Clinical experience with an injectable hormonal contraceptive depot - Larrañaga Leguía, Alfredo (2015)
207 highly fertile Peruvian females were studied with a long-acting hormonal contraceptive; this compound was a synthetic gestagen: Norethindrone enanthate; with a dose of 200 mg. every three months there were no pregnancies in a group of 134 patients. In 53 patients receiving the some dose every 4 months occurred 3 pregnancies, demonstrating the reversibility of the contraceptive mechanism. Side effects were observed in the first 3 months with the usual incidence for oral contraceptives, but they diminished to 2.9 % after this period of time. The authors remark the persistence of lactation and disappearance of dysmenorrhea that occurred in most of the patients.